Paramagnetic rim lesions predict greater long-term relapse rates and clinical progression over 10 years - Reeves, Jack A; Mohebbi, Maryam; Wicks, Taylor; Salman, Fahad; Bartnik, Alexander; Jakimovski, Dejan; Bergsland, Niels; Schweser, Ferdinand; Weinstock-Guttman, Bianca; Dwyer, Michael G; Zivadinov, Robert (Multiple sclerosis, 2024)
Paramagnetic rim lesions (PRLs) have been linked to higher clinical disease severity and relapse frequency. However, it remains unclear whether PRLs predict future, long-term disease progression. The study aimed to assess whether baseline PRLs were associated with subsequent long-term (10 years) Expanded Disability Status Scale (EDSS) increase and relapse frequency and, if so, whether PRL-associated EDSS increase was mediated by relapse. This retrospective analysis included 172 people with multiple sclerosis (pwMS) with 1868 yearly clinical visits over a mean follow-up time of 10.2 years. 3T magnetic resonance imaging (MRI) was acquired at baseline and PRLs were assessed on quantitative susceptibility mapping (QSM) images. The associations between PRLs, relapse, and rate of EDSS change were assessed using linear models. PRL+ pwMS had greater overall annual relapse rate (β = 0.068; = 0.010), three times greater overall odds of relapse (exp(β) = 3.472; = 0.009), and greater rate of yearly EDSS change (β = 0.045; = 0.010) than PRL- pwMS. Greater PRL number was associated with greater odds of at least one progression independent of relapse activity (PIRA) episode over follow-up (exp(β) = 1.171, = 0.009). Mediation analysis showed that the association between PRL presence (yes/no) and EDSS increase was 96.7% independent of relapse number. PRLs are a marker of aggressive ongoing disease inflammatory activity, including more frequent future clinical relapses and greater long-term, relapse-independent disability progression.